Absorption, metabolism, and excretion of [14C]-sebetralstat (KVD900) following a single oral dose in healthy male participants. (3rd July 2022) - Mutch, Peter; Bashir, Mohammad; Jung, Bonnie; Yi, Ping; Iverson, Matt
Abstract: Sebetralstat is an investigational oral plasma kallikrein inhibitor for the on-demand treatment of hereditary angioedema. Six healthy male participants received one dose of 600 mg (540 µCi) [ 14 C]-sebetralstat. Plasma concentrations of sebetralstat and levels of total radioactivity in plasma, urine, and faeces were determined. Metabolite profiles of radioactivity were generated, and major metabolites structurally characterised. Radioactivity was rapidly absorbed and was excreted with a mean of 95.8% (63.4% faeces; 32.4% urine) recovered by 216 h. Sebetralstat was the major drug-related component in urine and faeces, although metabolism predominated overall (main metabolites: M19 (des-[methoxy-fluoro-methylpyridine]-sebetralstat), M10 ( N -des-pyridone-sebetralstat-carboxylic acid), M3 (pyridine O -desmethyl-sebetralstat), and M34 (pyridine dioxy-dihydro-sebetralstat)). Sebetralstat was the main radiolabelled component in plasma (mean of 64.1% of the total radioactivity AUC0–24 ), followed by relatively low proportions of metabolites: M19 (7.10%), M3 (4.01%), and M10 (4.00%). Although M19 was >10% of the plasma radioactivity AUC0–24, in one participant it comprised a mean of <10% of AUC0–24 . Plasma levels of M19 were measured at the NOAEL dose in a rat toxicology study, where higher exposure was observed vs. that in humans. Given these findings and the lack of pharmacological activity of M19, it was concluded that there was no unique or disproportionate circulating metabolite in humans.